Chitin and Chitosan: Sustainable, Medically Relevant Biomaterials - J. Brigham, Christopher (International Journal of Biotechnology for Wellness Industries, 2017)
The polysaccharides chitin and chitosan are made up of monomer units of the amino sugars D-glucosamine and N-acetyl-D-glucosamine. The ratio of these two monomers dictates whether the polysaccharide is considered chitin or chitosan. Both polymers have unique properties and have uses in several diverse applications. In nature, chitin and chitosan primarily play a structural role. When purified from their producing organism, these polymers exhibit useful structural, chemical and biological properties. Chitin and chitosan have been used in several applications including biomedicine, food additives, cosmetics, and more. The charged chitosan polymer is especially effective in biomedical applications, as it has been demonstrated to possess antimicrobial properties. This review explores the properties of chitin and chitosan and how these biopolymers are used in a variety of healthcare and other applications.